The proposed designs modular of low-cost workers camp housed by using recycling container at the construction site / Jacksmith L. drecksson Claudius and Zainal Abidin Akasah - Claudius, Jacksmith L. drecksson; Akasah, Zainal Abidin (2019)
The project's research is to produce a modular design of low-cost shared houses from recycling containers at a built-in seat. The workers camp is a temporary home provided by the developer or contractor to facilitate the construction worker for the resting place. But the existing Malaysian Houses are often fired and there are also shared houses that are poorly supplied and do not comply with the Minimum Housing and Facilities Standard Act 1990. Apart from that, the placement provided is very narrow and the structure workers camp builds with wood and boards. Therefore, the objective of this project is to identify the types of containers to replace the structure of the shared houses, to produce suitable container designs for worker's camp, and to recommend the foundation and the calculation of gross pricing for the entire project proposal. There are five major processes which are data collection processes, design processes, analysis processes, basic preparation processes and the process of calculating the total gross cost of the project. Throughout the analysis process the total weight-loss, for the worker's camp is 37,220.22 KN/m2 . With the proposed site area of 24000mm x 2400mm x 7650mm there are 13 foundations available.